Comparative Characteristics of Paints Developed from Fly Ash, Copper Tailing and Blue Dust - Mohini Saxena; Sangeeta Tiwari; Payal Bakshi; Anusha Sharma (The Minerals, Metals and Materials Society, 2008)
"Recycling and reuse is perhaps the most favorable and beneficial way to solve the problem of industrial waste disposal. However, the use of industrial wastes like fly ash, tailings etc is in practice for brick manufacturing, land filling, embankments filling etc. These existing practices do not add enough value to the wastes. Moreover, some wastes may have very good potential to be incorporated in valuable products like paints. This study reveals about the value addition of industrial wastes like fly ash, copper tailing and blue dust as an extender in paints. Comparative properties and characteristics of these three wastes for application in paints are discussed. Fly ash, copper tailing and blue dust were characterized for physical, chemical and mineralogical properties and used in different paint formulation based on their potential to the particular application. Fly ash has been found very useful in enamel, primers and flat paints while copper tailing was found suitable in oil based paint formulations. The performance of fly ash and copper tailing paints were evaluated by comparing with those of conventional whiting extender. Blue dust was compared with conventional iron oxide for use in priming coats. The extender properties of these new material and paints prepared out of blue dust, fly ash, copper tailing, were found better than the existing related materials.IntroductionIndustrial development and environmental reforms should run parallel to benefit each other. This is the best policy, which must be adopted by industries for the sustainability of the current modern life. The high degree of industrialization and urbanization adds scads of waste resulting problem of pollution and challenges of their safe disposal. The nature of waste depends on the process that produces waste as its by-product. Therefore, policies/plans are prepared by keeping the view of possible potential hazards. Among the different wastes some are generated in the industries, which have great importance in the country’s economy, like fly ash waste from thermal power industry and mining waste. In India the total contribution of thermal power in the total electricity generation is more than 70% and it produces about 123 million ton of the fly ash annually [1]. On the other hand mining plus extraction of ferrous and nonferrous metals also produce waste in million tonnes of categories [2]. Since the generation of this waste is very high they cover large land area for their disposal and dumping [3]. The storage of this waste in the dumping sites for long time duration may cause problem of land, surface water, ground water and fertile soil contamination [4]. As far as Indian fly ash is concerned it does not contain toxic element over the limits of hazardous waste [5]. However, in general most of the metals deposits are found in the form of pyrite based ores. Mining wastes contain toxic elements e.g. heavy metals in varying amount, which get mobilized when pyrite get oxidized to sulphate producing sulphuric acid [6,7]. These ores contain very less amount of targeted metals in themselves thus they require extensive preprocesses for concentration of the metals [8]."